Thermal performance of Falkner Skan model (FSM) for (GOMoS2)/(C2H6O2-H2O) 50:50% nanofluid under radiation heating source - Mutasem Z. Bani-Fwaz; Adnan; Sami Ullah Khan; B. Shankar Goud; Tadesse Walelign; Kanayo Kenneth Asogwa; Iskander Tlili (Scientific Reports)
Abstract The hybrid base solvent water (H2O) and ethylene glycol (C2H6O2) are highly use in industrial applications due to excellent solvability. Addition of hybrid nanoparticles (GO-MoS2) augments the thermal conductivity of these fluids which ultimately make them very productive. Hence, the current study aims to develop and investigate the novel hybrid nanofluid model (GO-MoS2)/(C2H6O2-H2O) through MRW (moving riga wedge) and SRW (static riga wedge) cases. The traditional Falkner Skan Model (FSM) is modified using the novel effects of solar radiations, internal heating source and fixed magnets which is associated to the concept of Riga wedge. Further, the improved thermal-physical characteristics of hybrid nanofluids will use to enhance the thermal productivity. A mathematical model is developed for the flow situation of (GO-MoS2)/(C2H6O2-H2O) and treated numerically. The results furnished through graphical way and comprehensive discussion provided. It is examined that the movement of (GO-MoS2)/(C2H6O2-H2O) reduced for MRW and observed the rapid velocity near the surface. The heat generating source and solar radiations number enhanced the performance of (GO-MoS2)/(C2H6O2-H2O) and better predicted ranges for these parameters are observed from $$\:Q=\text{0.1,0.2,0.3,0.4}$$ and $$\:Rd=\text{1.0,2.0,3.0,4.0}$$ . Moreover, the boundary layer region becomes thin for heating source and it increased for stronger solar radiation effects. The nanoparticle amount of GO and MoS2 enhanced the model utilization while higher magnetic number and MRW number $$\:λ\:$$ controlled the thermal boundary layer. The results for the model dynamics are noticed dominant for MRW case as compared to SRW case.